2019
DOI: 10.1186/s40538-019-0147-2
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza and soil organic nitrogen: network of players and interactions

Abstract: Arbuscular mycorrhizal (AM) symbiosis is heavily and positively implicated in phosphorus (P) acquisition from soil to plants, including many important agricultural crops. Its role in plant nitrogen (N) nutrition is generally not as prominent or beneficial, with exception of some situations when N is available predominantly in organic forms. Yet the AM fungi (AMF) are, due to their poor exo-enzymatic repertoire, unlikely to degrade organic compounds on their own, therefore they possibly depend on other microorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 131 publications
(138 reference statements)
2
42
0
4
Order By: Relevance
“…In the field, root exudation in AM trees appears to result in increased inorganic N in the rhizosphere, whereas the extracellular enzymes stimulated by root exudates in EM root systems resulted in increased availability of amino acids . Hence, the traditional view is that an AM or AM-dominated dualmycorrhizal plant may be able to gain access to additional organic N and P by allowing colonization by EM fungi, but access to organic nutrients by AM fungi may have been underestimated (Jansa et al, 2019). This is a topic ripe to be examined using dual-mycorrhizal hosts.…”
Section: New Phytologistmentioning
confidence: 99%
“…In the field, root exudation in AM trees appears to result in increased inorganic N in the rhizosphere, whereas the extracellular enzymes stimulated by root exudates in EM root systems resulted in increased availability of amino acids . Hence, the traditional view is that an AM or AM-dominated dualmycorrhizal plant may be able to gain access to additional organic N and P by allowing colonization by EM fungi, but access to organic nutrients by AM fungi may have been underestimated (Jansa et al, 2019). This is a topic ripe to be examined using dual-mycorrhizal hosts.…”
Section: New Phytologistmentioning
confidence: 99%
“…Among fertilizers, the chemically synthesized nitrogen (N) was the main player, considering that its production via the Haber-Bosch industrial process accounted for about 2% of world’s annual energy output [ 24 ]. This massive production posed risks for environment and human health and once applied lead to soil quality loss [ 25 , 26 ]. Considering the ongoing climate changing and the consequent predicted stress scenarios that includes novel plant pathogens, intense abiotic stresses (e.g., drought and salinity) and low availability of organic N and phosphorus fertilizers, novel environmental friendly management options (e.g., smart-climate agriculture, including crop diversification and the use of beneficial root-associated microorganisms) are under scrutiny [ 26 , 27 ].…”
Section: Am Symbiosis-mediated Nitrogen Acquisition In Plantmentioning
confidence: 99%
“…Nowadays it is well recognized that AM symbioses are able to provide many ecosystem services to their hosts, including nutrients transfer from the soil (e.g., P, zinc, copper), although less importance to N cycling and acquisition have been imputed to AMF [ 26 ].…”
Section: Am Symbiosis-mediated Nitrogen Acquisition In Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that N concentration in AMF mycelium was higher (5%), as compared to the plant shoots and roots (� 1%) [65]. This could be explained by the substantial nitrogen demand of AMF for the synthesis of protein and chitin, the main constituents of their cell walls [66,67].…”
Section: Plos Onementioning
confidence: 99%